Hijrah and Look for Millenial Muslim Identity in Medan - Fakhrur Rozi; Syukur Kholil; Hasan Sazali (IAIN Ponorogo, 2021)
Hijrah process in Indonesia has evolved along with social media development, especially Instagram and YouTube that targetting certain generation groups. Islamic information on social media is also widely accessed by the public, especially millennial Muslims. Islamic information access is part of the look for the millennial Muslims identity in Medan, North Sumatra. This study analyzed aspects about using Islamic content, especially focusing on the Expectancy Value Model by Palmgreen about motive and media consumption satisfaction by the public. Using a phenomenological approach, the main finding of this study is that social media users access Islamic information actively based on the need for convenience in learning religion. The social media choice to access is dominated by Instagram and YouTube because they are more popular for millennial people. The look for millennial Muslim identities forms a relatively instant religious style because they position themselves more as consumers. Meanwhile, based on the value model expectation, two important things were found. First, the driving force of religious information consumption on the basis of an algorithm in which users are presented not only on the basis of searching for needs but also taken for granted that social media displays what is their consumers taste. Second, user satisfaction arises because the content that is accessed in terms of appearance, topics to diction is indeed targeting millennial Muslims who tend to be practical and ready to serve.